2006
DOI: 10.1080/10790268.2006.11753885
|View full text |Cite
|
Sign up to set email alerts
|

Aging After Spinal Cord Injury: A 30-Year Longitudinal Study

Abstract: Background/Objective: This longitudinal study investigated changes in life satisfaction, general health, activities, and adjustment over 3 decades among individuals with spinal cord injury (SCI).Participants: The cohort of participants was identified from outpatient records of a large Midwestern United States university hospital. In 1973, 256 individuals completed an initial survey. There were 5 subsequent follow-up surveys, with the most recent being in 2002. Seventy-eight participants completed materials on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 14 publications
3
36
1
3
Order By: Relevance
“…12,13 There were several similarities with the earlier research over shorter intervals. [7][8][9] In addition to the aforementioned survivor effect, there was a combination of favorable and unfavorable changes. Participants were clearly less active socially and continue to report a greater number of health problems, with corresponding diminished satisfaction in related areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 There were several similarities with the earlier research over shorter intervals. [7][8][9] In addition to the aforementioned survivor effect, there was a combination of favorable and unfavorable changes. Participants were clearly less active socially and continue to report a greater number of health problems, with corresponding diminished satisfaction in related areas.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several reports on a longitudinal cohort have been reported over a 30-year interval. [5][6][7][8][9] Changes in outcomes have evolved over time. There has been a mixed pattern of favorable and unfavorable changes, with general improvements in employment outcomes, overall adjustment, and satisfaction with employment and finances.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3]5 We found that LMP increases up to 15 years after SCI onset, but plateaus at around 40 with more than 80% of persons with SCI working, and this percentage falls afterwards. 8,19 Rather surprising is the low LMP of persons between 45 and 54, and who sustained their SCI 1 to 10 years before this study. (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…5 Frequently found factors associated with LMP in SCI are gender, marital status, education, disability severity, age, time since onset of SCI, social support, vocational counselling, perceived health and pain. 2,3,[5][6][7][8][9] However, the existing evidence on determinants of LMP in SCI is inconsistent. Although in some studies injury severity and gender are associated with LMP, others show the contrary.…”
Section: Introductionmentioning
confidence: 99%
“…The items were adapted from a checklist administered to unemployed participants in a previous study. 10 There is no data on test-retest reliability.…”
Section: Measurementioning
confidence: 99%